Design and experiment of fuzzy-PID based tillage depth control system for a self-propelled electric tiller - Xiao, Maohua; Ma, Ye; Wang, Chen; Chen, Junyun; Zhu, Yejun; Bartos, Petr; Geng, Guosheng (International Journal of Agricultural and Biological Engineering, 2023)
The research on the self-propelled electric tiller is vital for further improving the quality and efficiency of greenhouse rotary tillage operation, reducing the work intensity and operation risk of operators, and achieving environmentally friendly characteristics. Most of the existing self-propelled tillers rely on manual adjustment of the tillage depth. Moreover, the consistency and stability of the tillage depth are difficult to guarantee. In this study, the automatic control method of tillage depth of a self-propelled electric tiller is investigated. A method of applying the fuzzy PID (Proportional Integral Derivative) control method to the tillage depth adjustment system of a tiller is also proposed to realize automatic control. The system uses the real-time detection of the resistance sensor and angle sensor. The controller runs the electronically controlled hydraulic system to adjust the force and position comprehensively. The fuzzy control algorithm is used in the operation error control to realize the double-parameter control of the tillage depth. The simulation and experimental verification of the system are conducted. Results show that the control system applying fuzzy PID can improve the soil breaking rate by 3% in the operation process based on reducing the stability variation of tillage depth by 24%. The control strategy can reach the set value of tillage depth quickly and accurately. It can also meet the requirement of tillage depth consistency during the operation. Keywords: fuzzy PID, self-propelled electric tiller, tillage depth, electro-controlled hydraulic system, comprehensive adjustment of force and position DOI: 10.25165/j.ijabe.20231604.8116 Citation: Xiao M H, Ma Y, Wang C, Chen J Y, Zhu Y J, Bartos P, et al. Design and experiment of fuzzy-PID based tillage depth control system for a self-propelled electric tiller. Int J Agric & Biol Eng, 2023; 16(4): 116-125.